Tectonically induced Quaternary drainage diversion in the northeastern Aegean - Okay, NILGÜN; Okay, ARALI. (Geological Society of London, 2002)
The Maritsa River in the Balkans, over 500 km long, flows at present into the northern Aegean Sea. Geological and geomorphological data indicate that it was flowing into the Marmara Sea until about 1.5 Ma, and was diverted into the Aegean Sea following coseismic uplift along the North Anatolian Fault. Seismic reflection sections in the Marmara Sea indicate the presence of up to 2.5 km thick fluviatile to limnic Upper Miocene–Quaternary sediments, probably supplied by a Palaeo-Maritsa river. The drainage diversion cut off the sediment supply, with the result that the terrigeneous sediments of the Marmara Sea were depressed to a water depth of 1150 m.